Design and fabrication of ventilated cat litter box - Muhammad 'Afif, Mohamed Azmi (2011)
Manufacturing process is a process of converting raw material into product. It can be described the transformation of materials into terms of greater value by means of one or more processing and/or assembly operations. The study of manufacturing was very important in order to carry out this project to ensure that student understand on what are needs to do. This project is focused on designing and fabricating the Ventilated Cat Litter Box. The main objective in this project is to design an cat box that has ventilation system apply on it. This project involves the process of designing the ventilated cat litter box by considering the shape, functionality, portability for people to use it and the manufacturing cost. The material of this design is easy to gain it, because it only using rectangular hollow steel and Perspex. So that the method joining that can be compatible in assembled this ventilated cat litter box is welding process and joining the Perspex to the frame is by using screw. This project also required analysis to ensure the strength and safety of the product meet the user need. After all processes had done, the development of this ventilated cat litter box may help us to understand the fabrication and designing process involved in this project. The manufacturing process included in this project is marking and cutting of material, machining, drilling, joining and finishing.